Atividades musicais e corporais entre jovens e adolescentes na escola pública: pertencimento, subjetivação e cultura - Lavacca, Antonio Belforte (2018)
From the development of activity workshops that encompassed the universes of music and body language, some students of a public school in the periphery of a medium-sized city have set out a few main axes: on the field of belonging, subjectivation and culture, we sought to dialogue with some artistic practices carried out collectively, with the goal of analyzing the possible contributions of the practices in the daily lives of the participants. The age range of adolescents and young people goes from 8 to 18 years old. It is a qualitative research that had a hybrid methodological procedure: the usage of field diaries, the usage of questionnaires to assist the characterization of the participants, interviews with teachers, school management, a mother and materiality of criticisms and artistic products made by adolescents and young participants that symbolized in practical results part of the actions in the field. The activity workshops are justified as part of the methodology. The results analyzed constitutive elements and workshops of activities and demonstrated that changes occurred along the students' daily lives when it comes to the collective meaning, affection and the construction of self through experience, the humanized relations and dialogue. From the point of view of employees, managers and parents, such as musical and corporal expression practices, such as workshops for contributory activities other than meetings, in other disciplines, in the community and at school, the socialization skills are generally unknown, of logical and behavioral reasoning, for example. The final considerations punctuated which were used in the practices of collective musical practices in the life of the participants. It has been observed that there has been an improvement in the relationship among themselves and colleagues, family, and they have shown a greater interest in sharing experiences and affections. The space where the workshops took place turned into a space of caring and collective belonging: a place where adolescents and young people could live and demonstrate their particularities, welcomed among all members.